Evolução do dimorfismo estaminal e sua correlação com atributos florais e reprodutivos em uma família com flores de pólen - Melo, Lílian Rodrigues Ferreira de (2019)
Animal pollination is believed to be one of the causes of the high diversity of angiosperms since the selective pressure exerted by pollinators leads to modifications in floral structure and reproductive strategies. The “Division of labor hypothesis” proposes that there are different roles in dimorphic stamens within the same flower. The smaller stamen produces pollen to feed pollinators (e.g. bees) and the larger stamens produces pollen essentially to plant reproduction. Stamen dimorphism is observed in at least 20 families of angiosperms and is related to poricidal anthers and enantiostily in pollen-rewarding flowers. However, there is a lack of knowledge about the evolution as well as the selective pressures that led to stamen dimorphism inside clades in which stamen dimorphism is frequent. We investigate stamen differentiation process over the evolutionary time of Melastomataceae. We test the correlation of stamen dimorphism with other floral traits as well as with plant reproductive system on an evolutionary framework. The phylogenetic data was gathered in GenBank. The more frequent molecular markers were chosen, including two ribosomal spacers, two plastome genes and four plastome spacers. Best nucleotide substitution model fit was evaluated in PartitionFinder 2. A Bayesian analysis was conducted to infer the family phylogeny and divergence times. A literature review was made in order to gather morphological data. We search species descriptions that presented stamens, styles and petals lengths. Afterwards, a stamen dimorphism index (SDI) was created based in stamen length information. Phylogenetic signal (Blomberg's K) was estimated for all variables. We also performed ancestral trait reconstruction as well as evolutionary correlation analysis in order to answer if stamen dimorphism evolution is related to reproductive system and flower size. Despite Melastomataceae ancestral flower probably had stamens with equal sizes, stamen dimorphism appeared at least 12 times along its evolutionary history. All the traits presented low phylogenetic signal indicating that flower traits are very labile. Plants that depend on pollinators to reproduce present higher stamen dimorphism than autonomous plants. Our results indicate that stamen dimorphism has evolved several times in flowers of Melastomataceae. Stamens dimorphism is positively correlated with the increase of the petal throughout the evolutionary history. The selection pressure exerted by the bees on plants that depend on these pollinators for reproduction favored the stamens dimorphism and this pressure seems to be even larger in large flowers. The rates of diversification, extinction and speciation are higher in species with stamens dimorphism, indicating that specialized pollinators may be direct agents of the process of flowering plant diversification by means of an increased specialization in floral morphology.